A low knee voltage and high breakdown voltage of 4H-SiC TSBS employing poly-Si/Ni Schottky scheme. (February 2018) - Kim, Dong Young; Seok, Ogyun; Park, Himchan; Bahng, Wook; Kim, Hyoung Woo; Park, Ki Cheol
Abstract: We report a low knee voltage and high breakdown voltage 4H-SiC TSBS employing poly-Si/Ni dual Schottky contacts. A knee voltage was significantly improved from 0.75 to 0.48 V by utilizing an alternative low work-function material of poly-Si as an anode electrode. Also, reverse breakdown voltage was successfully improved from 901 to 1154 V due to a shrunk low-work-function Schottky region by a proposed self-align etching process between poly-Si and SiC. SiC TSBS with poly-Si/Ni dual Schottky scheme is a suitable structure for high-efficiency rectification and high-voltage blocking operation.